A Linguistic Analysis of Verbal Phrase Construction in Totto-Chan: The Little Girl at the Window - Kusmiarti, Reni; Yuniarti, Ira; Rustinar, Eli; Wihnata, Andre; Anugrah, Trisna (UNIB Press, 2025)
Nominal phrases are important elements in grammar that form sentence structures. In linguistic studies, the analysis of verb phrase construction is important to understand the author's language style and convey the meaning of a text. This study aims to identify the construction of verb phrases in the novel Totto-Chan: The Little Girl at the Window by Tetsuko Kuroyanagi using a linguistic approach. This research uses a qualitative descriptive method. Data were collected through text analysis on sentences containing verb phrases, the data source is the novel Totto-Chan: The Little Girl at the Window by Tetsuko Kuroyanagi. The data were analyzed using the documentation technique, namely by reading and identifying sentences containing verb phrases in the novel. Each verb phrase found was recorded and categorized based on its type. After the data was collected, the verb phrases were classified based on their construction. The data that has been classified is then analyzed using syntactic theory to identify the construction of verb phrases and then interpreted to understand the construction of verb phrases in building the narrative of the story. Then draw conclusions based on the findings. The research found two types of main phrase construction, namely coordinative phrases 161 data, and subordinative phrases 350 data with several types of subordinative phrases, namely subordinative verbal phrases structured Adv + V as much as 198 data, subordinative verbal phrases structured V + Adv 57 data, subordinative verbal phrases structured V + N 71 data, subordinative verbal phrases structured V + A 24 data.